PENGARUH BRAND EQUITY TERHADAP PURCHASE INTENTION MELALUI BRAND PREFERENCE PADA PRODUK PT. SUNLIFE FINANCIAL DI SURABAYA - SANJAYA, EDWIN (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
Research carried out aimed to examine the relationship between Brand Equity and Purchase Intention by mediating Brand Preference at PT. Sunlife Financial in Surabaya. This study uses SEM (Structural Equation Modeling), sampling technique in this study using a non-probability sampling using the method of sample selection based on considerations of judgment sampling with particular reference to the sample in this study, amounting to 100 people based on the characteristics of the sample are people who know insurance services in PT. Sunlife Financial in Surabaya. The results showed that the positive effect on Brand Equity, Brand Preference, Brand Equity influence on Purchase Intention is positive, the effect of Brand Preference to Purchase Intention is positive. Brand Preference positive influence as mediating the relationship between Brand Equity to Purchase Intention in PT. Sunlife Financial in Surabaya. Research conducted that analyzed the relationship of Brand Equity on Brand Preference interest in purchasing through the people who know the insurance service PT. Sunlife Financial in Surabaya.